Clinical and functional outcomes of pediatric elbow dislocations: Level 1 tertiary trauma center experience - Agar, Anıl; Şahin, Adem; Gülabi, Deniz; Ertürk, Cemil (Journal of Surgery and Medicine, 2022)
Background/Aim: Traumatic elbow dislocations have been reported as uncommon in pediatric population. Because of low frequency, there are not many studies on the subject in the literature. The aim of this study was to retrospectively evaluate the radiological and functional results of pediatric patients treated for elbow dislocations in a level-1 tertiary trauma center and to compare the results of simple and fractured dislocations. Methods: This is a retrospective cohort study of a single center experience diagnosed with pediatric elbow dislocations between 2015 and 2019. The cases were evaluated by dividing them into two groups as simple dislocations and fracture dislocations. Demographic features, injury mechanism, treatment, complications and Mayo elbow performance score (MEPS) were evaluated. Results: Fifty-seven patients, (46 male/ 11 female), were included in the study, with a mean age of 11.1 (3-15) years. Mean follow up time was 27.2 (12-51) months. While 30 patients had fracture dislocations, 27 patients had simple dislocations. Of 30 patients with fracture dislocations, 19 were operated. Nonunion in the medial epicondyle in five patients, AVN (avascular necrosis) in radial head in two patients, heterotrophic ossification in one triceps, and recurrent dislocation in one patient were detected. According to MEPS, 42 (73%) of 57 patients were excellent, 12 (21%) good, one (2%) moderate, and two (4%) poor. According to MEPS, functional results of simple dislocations were found to be better than those of fracture-dislocations, and this result was statistically significant (P<0.05). Conclusion: Elbow dislocations in children can be treated with good results if they are accurately diagnosed and if concentric stable reduction of the elbow as well as stable osteosynthesis of displaced fractures can be achieved. Simple dislocations are easier to manage and functional results are better, whereas the treatment of fractured dislocations is more complex and complications are more common in follow-up.